1999
DOI: 10.1063/1.477833
|View full text |Cite
|
Sign up to set email alerts
|

Optical line shapes of dynamically disordered ring aggregates

Abstract: We study the absorption line shape caused by Frenkel excitons in one-dimensional ring-shaped molecular aggregates, such as circular light-harvesting systems, subjected to dynamic disorder with a finite correlation time. We focus on dichotomic noise and show that for arbitrary orientations of the molecular transition dipoles relative to the ring, the absorption spectrum may be calculated exactly by solving two very similar sets of 2N coupled linear equations of motion, where N is the number of molecules in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…For the higher-energy (k ¼ AE1) absorption line, the narrowing factor is less than for the k ¼ 0 state, as a consequence of the disorder-induced splitting within the degenerate pair. In the case of fast dynamic energy disorder, it has been shown that the higher-energy (k ¼ AE1) line is twice as broad as the low-energy (k ¼ 0) one [23], while in the case of static energy disorder, the difference is a factor of ffiffi ffi 2 p [24]. Moreover, the higher line is also broadened by energy relaxation to the lower state.…”
Section: Theory Of Spectral Behavior Of Cylindrical Jaggregatesmentioning
confidence: 89%
“…For the higher-energy (k ¼ AE1) absorption line, the narrowing factor is less than for the k ¼ 0 state, as a consequence of the disorder-induced splitting within the degenerate pair. In the case of fast dynamic energy disorder, it has been shown that the higher-energy (k ¼ AE1) line is twice as broad as the low-energy (k ¼ 0) one [23], while in the case of static energy disorder, the difference is a factor of ffiffi ffi 2 p [24]. Moreover, the higher line is also broadened by energy relaxation to the lower state.…”
Section: Theory Of Spectral Behavior Of Cylindrical Jaggregatesmentioning
confidence: 89%
“…The predicted excitation level structure [6,10–13] of the lowest‐energetic one‐excitation band of an 18 BChls a numbered, completely ordered circular aggregate (i.e. identical Q y excitation energy of the individual BChls a ) of C 9 symmetry is shown in Fig.…”
Section: Theoretical Predictions On Excitation Spectra Of Circular Agmentioning
confidence: 99%
“…Molecular aggregates including photosynthetic [1][2][3][4][5][6][7][8] and other biological pigment-protein complexes [9][10][11] and optoelectronic devices [12][13][14] have been extensively investigated by using spectroscopic methods and theories [15][16][17][18][19][20][21][22][23]. In such aggregates, monomeric molecular units are electronically coupled to each other to produce a collective spectral properties such as line narrowing, super-radiance, and coherent or incoherent excitation energy transfer.…”
Section: Introductionmentioning
confidence: 99%